Performance evaluation of CFD codes in building energy and environmental analysis - Gaspar, Pedro Dinis (2003)
Experimental studies in building energy usage and environmental analysis are very time consuming and expensive, and require sophisticated sensors and instrumentation techniques. So, there has been great interest in developing Computational Fluid Dynamics (CFD) computer codes to improve building design and HVAC systems. The majority of these CFD programs are based on the solution of Navier-Stokes equations, the energy equation, the mass and concentration equations as well as the transport equations for turbulent velocity and its scale. The aim of this study is to present the advantages, applicability and potentialities of CFD in building design. The advantages and the performance of (two) commercial CFD codes and an academic CFD code develop for this purpose are evaluated. The codes were applied to predict typical situations of the airflow in buildings and the predictions were compared with experimental results.